Safety and immunogenicity profiles of an adjuvanted seasonal influenza vaccine in Guatemalan children - Solares, Adib Rodriguez; Aragon, Carlos Grazioso; Pivaral, Rodolfo Urruela; Prado-Cohrs, David; Sales-Carmona, Victor; Pellegrini, Michele; Groth, Nicola (The Journal of Infection in Developing Countries, 2014)
Introduction: The efficacy of non-adjuvanted seasonal influenza vaccine in young children is considered to be suboptimal. This study compared the safety and immunogenicity profiles of MF59-adjuvanted, trivalent, influenza vaccine (ATIV) and non-adjuvanted, trivalent, influenza vaccine (TIV) in Guatemalan children (N = 360) between 6 and < 60 months of age. Methodology: Children received two doses of ATIV or TIV administered four weeks apart. Solicited adverse reactions were recorded for seven days after each vaccination. Serious adverse events were recorded throughout the entire study period. Antibody responses were assessed by hemagglutination inhibition (HI) assay at baseline, four weeks after administration of the first vaccine dose, and three weeks after administration of the second dose. Results: Both ATIV and TIV were well tolerated, with similar rates of solicited reactions and adverse events observed in response to both vaccines. MF59-adjuvanted vaccine induced considerably higher antibody titers than did TIV. After two doses, the B strain-specific antibody response to TIV was insufficient to meet the Center for Biologics Evaluation and Research (CBER) licensure criterion for seroprotection, whereas responses to the MF59-adjuvanted vaccine met the seroprotection criterion against all three strains. Cross-reactive antibody responses to MF59-adjuvanted vaccine met the CBER seroprotection criterion against all three strains after two doses; B strain-specific heterologous responses to non-adjuvanted TIV were inadequate. Conclusions: The MF59-adjuvanted seasonal influenza vaccine was well-tolerated and highly immunogenic in children 6 to < 60 months of age, inducing seroprotective antibody titers against both the vaccine strains and antigenically distinct heterologous strains.